KERJA SAMA SELATAN-SELATAN DAN MANFAATNYA BAGI INDONESIA - Adirini Pujayanti (Sekretariat Jenderal DPR RI, 2015)
Indonesian foreign policy is always mentioned by the country’s leaders for the sake of achieving national interest. Under the SBY administration, its implementation is carried out by introducing its soft power policy, by offering foreign aids, performing its new role as donor to developing countries through South-South Cooperation (SSC). It is considered by the Indonesian leaders that performing an active role in SSC would give political benefit or positive image for the country. This paper resulted from research report conducted in 2014, adopting a qualitative method of analysis with collecting data activities in Surabaya and Gorontalo. The research is aimed to know how far Indonesia can take benefits from SSC. Its finding concludes that the country’s involvement is intended to gain political support from developing countries for the country’s political interest in international arena. Unfortunately, it has not yet given significant contribution for the country’s economic development, especially in the regions.